Bed‐sharing by breastfeeding mothers: who bed‐shares and what is the relationship with breastfeeding duration?. (11th March 2016) - Ball, Helen L.; Howel, Denise; Bryant, Andy; Best, Elspeth; Russell, Charlotte; Ward‐Platt, Martin
Abstract: Aim: To explore the link between breastfeeding duration and bed‐sharing frequency among women reporting a prenatal intention to breastfeed. Methods: About 870 participants in a randomised breastfeeding trial, recruited at mid‐pregnancy, provided weekly snapshots of breastfeeding and bed‐sharing behaviour for 26 weeks following birth. Strength of prenatal breastfeeding intent was recorded at recruitment using Likert‐type scales. Results: Outcomes were frequency of bed‐sharing at home for at least one hour per week, and time to cessation of breastfeeding. There were insufficient data to classify bed‐sharing pattern in 192/870 (22%) of mothers. Of the remainder, 44% (299/678) of participants 'rarely' or 'never' bed‐shared, 28% (192/678) did so 'intermittently' and 28% (187/678) did so 'often'. These three groups did not differ significantly in marital status, income, infant gestational age, maternal age or delivery mode. Significantly, more participants who bed‐shared 'often' reported strong prenatal breastfeeding intent (70% vs. 57% and 56% for 'intermittent' and 'rare' bed‐share groups) and attached high prenatal importance to breastfeeding (95% vs. 87% and 82%). Significantly, more women who bed‐shared frequently were breastfeeding at 6 months (p < 0.0001) than those who intermittently or rarely/never bed‐shared. Conclusion: Women with strong motivation to breastfeed frequently bed‐share. Given the complex relationship between bed‐sharing and sudden infant death syndrome (SIDS) appropriate guidance balancing risk minimisation with support for breastfeeding mothers is crucial. Abstract :